(untitled) (Journal of the College of Basic Education, 2022)
The issue of Syria and Lebanon from the First World War 1914 to the French Mandate in 1920 is considered one of the important topics that discussed the reality of the political situation in both countries, as the Syrian policy was characterized as a policy that calls for unity and the building of a unified Arab government with Damascus as its capital and Prince Faisal as its king, while politics tended The Lebanese move away from the issue of the Syrian unity and its attempt to disengage from Syria and achieve independence. Therefore, the nature of the Syrian-Lebanese relations and conditions was and still is one of the most important topics that deserve research in my estimation, which encouraged me to write about it.